2013
DOI: 10.1186/1756-0500-6-56
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suitable reference genes for gene expression studies in porcine PBMCs in response to LPS and LTA

Abstract: BackgroundAs an in vitro model porcine peripheral blood mononuclear cells (PBMCs) is frequently used as for immunogenetic research with the stimulation of bacterial antigens. To investigate the immunocompetence of PBMCs for recognition of Gram-positive and Gram-negative bacteria and in order to dissect the pathogenesis of diseases, gene expression assay is most commonly used. The gene expressions are required to normalize for reference genes which have tremendous effect on the results of expression study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Clean reads quality metrics are shown in (Table 1). We used StringTie [12] to reconstruct transcripts, then we used Cuffmerge (Cufflinks tools [13]) to bring together the refactoring information for all our samples, and used Cuffcompare to compare reconstructed transcripts to reference annotation. Subsequently, we mapped clean reads to a reference using Bowtie 2 [14], followed by the gene expression level calculation using RSEM [15].…”
Section: Rnaseq Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clean reads quality metrics are shown in (Table 1). We used StringTie [12] to reconstruct transcripts, then we used Cuffmerge (Cufflinks tools [13]) to bring together the refactoring information for all our samples, and used Cuffcompare to compare reconstructed transcripts to reference annotation. Subsequently, we mapped clean reads to a reference using Bowtie 2 [14], followed by the gene expression level calculation using RSEM [15].…”
Section: Rnaseq Data Analysesmentioning
confidence: 99%
“…To validate the accuracy of the DGE result, 20 of biologically relevant genes from the same RNA used for DGEs sequencing were randomly selected. Primer premier 5.0 was used to design the targeted genes primers ( Supplementary Table 1) and the internal reference gene (GAPDH) was selected based on the published reference gene GAPDH (Genbank: 396823) [12].…”
Section: Genes Expression Analysis By Qrt-pcrmentioning
confidence: 99%
“…This is reasonable, as from the host's point of a view an invading microorganism is simply undesirable, whatever its reaction to the Gram stain. Indeed, modulo a few detailed differences [30], and certainly for our present purposes, it seems that LTA is indeed broadly equivalent to LPS in terms of its ability to stimulate an innate immune response [31][32][33].…”
Section: Introductionmentioning
confidence: 77%
“…Using these statistical algorithms, a number of suitable reference miRNAs have been identified for quantifying miRNAs expression in humans (Doyle et al, 2002;Pfaffl et al, 2004;Guenin et al, 2009;Shen et al, 2011;Lamba et al, 2014) and in livestock species (Gu et al, 2011;Wessels et al, 2011;Timoneda et al, 2012;Li et al, 2014). Previous studies suggested that different mRNA reference genes are required for mRNA gene expression studies in porcine PBMCs at different stages or with different immunological stimulants (Ju et al, 2011;Cinar et al, 2013). While many reference genes suitable for mRNA expression studies have been identified in porcine PBMCs, no well-established reference miRNAs have been investigated.…”
Section: Discussionmentioning
confidence: 98%